Modelling of end-use electricity consumption and saving potential in household sector in northern Thailand - Kittikun Poolsawat (2018)
Copyright © 2017, AIDIC Servizi S.r.l. This study presents the actual state of electricity consumption in the household sector in northern region. The characteristics of household electricity consumption was considered to be an essential information for overview estimation of energy usage. The feasibility of energy conservation by improving end-use electricity energy efficiency was investigated. A questionnaire interview survey of 2,500 households concerning 36 kinds of appliances was conducted covering urban and rural areas in northern region in 2016 to identify the characteristics of household electricity consumption. The survey covers three areas: (i) household characteristics, (ii) dwelling characteristics, and (iii) appliances. The survey results were extrapolating, by using the energy model which implies the majority of household electricity consumption in the area level, to estimate the whole electricity consumption for northern region. The result overall electricity consumption in the household in northern region will be 5,604.10 GWh in the year 2016 shows with a make-up of refrigerator (32.10 %), air conditioner (18.04 %), light bulb (17.72 %), television (9.36 %), fan (7.63 %), rice cooker (5.19 %), iron (4.57 %), water heater (3.07 %) and washing machine (2.32 %). Around 16.14 % of electricity consumption, 847.24 GWh or 479.96 kt CO 2 , could be reduced by means of replacement with higher efficiency appliances. The electricity saving potentials are 65.23 % by changing fluorescent light bulb (FL) to Light Emitting Diode bulb (LED), 44.83 % by changing Cathode Ray Tube television (CRT) to LED television, 1.58 % for rice cooker, 1.53 % for iron, 1.03 % for washing machine, 0.78 % for water heater, 0.70 % for fan, 0.29 % for refrigerator and 0.23 % for air conditioner. The greenhouse gas mitigation from energy reduction potential including the policy recommendation are also raised.